(untitled) (LACCEI, 2024)
In this paper, a descriptive quantitative research is carried out on the impact of digital migration derived from the COVID-19 pandemic on the frequency of use of ICT resources in the teaching activity of university professors in Peru. The main objective is to identify differences in the aforementioned impact according to the area of ​​knowledge of the teachers. A questionnaire designed by the authors has been used to measure the frequency of ICT use before and after the COVID-19 pandemic and the answers have been statistically analyzed. As a result, it has been obtained that the pandemic has caused a significant increase in the use of ICTs in all dimensions of teaching activity, especially those in which they are used less regularly. In addition, this increase has been greater among professors of humanistic-social areas than among professors of scientific-technical areas.